2012
DOI: 10.1177/2045125312436572
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain-derived neurotrophic factor, vascular endothelial growth factor and leptin levels in patients with a diagnosis of severe major depressive disorder with melancholic features

Abstract: Abstract:Objective: Brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF) and leptin have been hypothesized to be involved in the neurobiology of depression. The aim of this study was to investigate BDNF, VEGF and leptin levels in patients with severe melancholic depression. Methods: A total of 40 drug-free patients with major depressive disorder (MDD) with melancholic features and 40 healthy controls were included in the study. Demographic information, psychiatric evaluation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 76 publications
(116 reference statements)
5
31
0
Order By: Relevance
“…However, there are considerable discrepancies among studies investigating VEGF in depression. While some studies have reported increased VEGF mRNA (Berent et al, 2014;Iga et al, 2007), serum (Berent et al, 2014;Kahl et al, 2009) or plasma (Lee and Kim, 2012;Takebayashi et al, 2010) levels in patients with MDD, others have found significant decreases in VEGF peripheral levels in depression (Dome et al, 2009;Isung et al, 2012;Katsuura et al, 2011) or no difference between patients with MDD and healthy controls (Kotan et al, 2012;Ventriglia et al, 2009). A recent review assessing clinical studies on VEGF and depression speculated that elevation in VEGF levels in patients with MDD appears to be due to the response to the perceived stress associated with depression resulting in an attempted neuroprotective effect, whereas decreased levels of VEGF seem to be observed in treatment-resistant depressed patients whose brains are less able to undergo neurogenesis processes (Clark-Raymond and Halaris, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…However, there are considerable discrepancies among studies investigating VEGF in depression. While some studies have reported increased VEGF mRNA (Berent et al, 2014;Iga et al, 2007), serum (Berent et al, 2014;Kahl et al, 2009) or plasma (Lee and Kim, 2012;Takebayashi et al, 2010) levels in patients with MDD, others have found significant decreases in VEGF peripheral levels in depression (Dome et al, 2009;Isung et al, 2012;Katsuura et al, 2011) or no difference between patients with MDD and healthy controls (Kotan et al, 2012;Ventriglia et al, 2009). A recent review assessing clinical studies on VEGF and depression speculated that elevation in VEGF levels in patients with MDD appears to be due to the response to the perceived stress associated with depression resulting in an attempted neuroprotective effect, whereas decreased levels of VEGF seem to be observed in treatment-resistant depressed patients whose brains are less able to undergo neurogenesis processes (Clark-Raymond and Halaris, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In one report, the authors found significantly lower VEGF levels in the peripheral blood of MDD patients than in healthy controls (Carvalho et al, 2013). However, other studies have reported no difference between the levels in peripheral blood of MDD patients and healthy controls (Dalby et al, 2013;Dome et al, 2009;Fornaro et al, 2013;Kotan et al, 2012;Ventriglia et al, 2009). These inconsistent findings may be due to many confounding factors, such as different study design, physical illness, age, gender distribution, medical history, length of illness, previous exposure to antidepressants, severity of depression, or sample source (plasma, serum, or whole blood).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, we re-included one article in the meta-analysis of correlations between VEGF and severity of disease (Isung et al, 2012). The results of the literature search are listed in Table 1 (Berent et al, 2014;Carvalho et al, 2014Carvalho et al, , 2013Clark-Raymond et al, 2014;Dalby et al, 2013;Dome et al, 2009;Elfving et al, 2014;Fornaro et al, 2013;Galecki et al, 2013a;Kahl et al, 2009;Kotan et al, 2012;Lee and Kim, 2012;Lu et al, 2013;Schweiger et al, 2008;Takebayashi et al, 2010;Ventriglia et al, 2009). …”
Section: Studies Included In the Current Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations